Characterization of the Key Material for Elimination of PM2.5 Particles in the Atmosphere - Bo Qiu; Qingshan Li; Wei Hong; Guangzhong Xing (Journal of Spectroscopy)
In recent years, with the gradual deterioration of air quality and with the more and more frequency of haze weather phenomenon, it intrudes into the human body and brings great harm to human health when people are unprepared. The basic theory that anion could purify air and eliminate positive ion explains that anion balata modified bitumen could reduce PM2.5, and the number of anion pavement release relates to the air purification. At the same time, building materials plaza and pavement materials with many functions were designed which can release negative ions, eliminate PM2.5 particles, and decompose harmful components of fuel vehicle exhaust.